Conduction mechanism of donor and acceptor doped sodium niobate-based ceramics. Issue 21 (1st November 2022) - Lu, Luting; Li, Linhao; Ren, Pengrong; Che, Xiuzi; Zhao, Gaoyang
Abstract: Recently, NaNbO3 (NN) has become a hot topic of current research due to its antiferroelectric energy storage properties, which demand that the ceramics withstand large applied electric fields. The breakdown strength is dependent on conduction properties, but there is limited research on the conduction mechanisms of NN. Here we report that A-site donor-doping of Bi 3+ (Bix Na1-3x NbO3 ) and B-site acceptor-doping of Mg 2+ (NaNb1-2/5y Mgy O3 ) in NN lead to dramatic changes in the magnitude of the bulk conductivity (σb ) and the conduction mechanism of NN ceramics. Undoped NN exhibits mixed conduction behavior with an oxide ion transport number (tion ) of ∼0.44, and σb of ∼10 −6  S/cm at 600 °C. A low level of Bi 3+ doping (x = 0.06) suppresses the NN mixed conduction mechanism to electron conduction (tion  ∼ 0), and the bulk conductivity increases significantly, σb  > 10 −4  S/cm at 600 °C. On the other hand, Mg 2+ doping (y = 0.06) samples mainly change the σb, with the mixed ion/hole conduction (tion  ∼ 0.43) and σb  > 10 −4  S/cm at 700 °C. The results show that the conductivity of NN increases and exhibits different conduction mechanisms with the doping of Bi 3+ and Mg 2+ . Aliovalent doping is not beneficial to improving the insulation properties. Thus, this work provides theoretical guidance for the study of energy storage characteristics and the suppression of leakage behavior of high-temperature dielectric capacitors.